Effectiveness of Rheumatic Exercise in Reducing Joint Pain among the Elderly: A Quasi-experimental Approach - Syahla Rahadatul Aisyi; Mochamad Ari Fardiansyah; Deasy Afrieani (Jurnal Keperawatan Olahraga, 2025)
Introduction: Joint pain is a common complaint among the elderly, primarily due to degenerative changes in the musculoskeletal system. Non-pharmacological interventions, such as rheumatic exercise, have been shown to effectively reduce joint pain. Aims: This study aimed to assess the effect of rheumatic exercise on the joint pain scale among elderly residents at UPTD Pusat Pelayanan Sosial Griya Lansia.Methods: A quasi-experimental design was employed using a two-group pre-test–post-test approach. The sample included 30 elderly individuals experiencing joint pain, divided into two groups: 15 participants in the intervention group (rheumatic exercise) and 15 in the control group (elderly exercise). Data were analyzed using paired t-tests and independent sample tests. Results: The average joint pain score in the intervention group decreased from 4.53 to 3.07, while in the control group, it decreased from 5.07 to 3.53. Statistical analysis revealed a significant reduction in joint pain within both groups (p < 0.05); however, no statistically significant difference was found between the two groups (p = 0.756). Conclusion: Both rheumatic and elderly exercise programs were effective in reducing joint pain among older adults. These findings support the implementation of regular exercise programs as non-pharmacological interventions in social care settings. Future research is encouraged to explore additional influencing variables, such as nutritional intake and emotional well-being